Analisis Determinan Pertumbuhan Ekonomi dari Sisi Pendapatan Daerah di Provinsi Jambi Selama Tahun 2017-2021 - Dessy Anggraini; Neneng Sudharyati; Risma Dwinna Pratiwi; Nanda Rahayu Selviana (Ekonomis: Journal of Economics and Business, 2023)
This study aims to see how big the influence of regional original income, general allocation funds, special allocation funds, and profit sharing funds on economic growth in Jambi Province. The type of data used in this research is in the form of secondary data obtained from the Central Bureau of Statistics using cross-sectional data from 11 regencies/cities in Jambi Province and time series data for the 2017-2021 period. The data analysis used is panel data analysis with the fixed effect model (FEM). The results of the research show that of the four variables used in this study, namely the variable regional original income, general allocation funds, special allocation funds and profit-sharing funds. The general allocation fund and special allocation fund variables show a significant influence on economic growth, namely 0.0058 and 0.0003 respectively with a 95% confidence level. The variables of regional original income and revenue sharing show no significant effect on economic growth, namely 0.1980 and 0.2047 respectively with a 95% confidence level. The coefficient of determination is 0.9948, meaning that 99.48 percent of the variation in economic growth can be explained by the independent variables in the model, namely local revenue, general allocation funds, special allocation funds, and profit sharing funds, while the remainder is 0. 52 percent is explained by other variables outside the research.